2006
DOI: 10.1159/000092952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Outcomes of Patients with COPD Exacerbation with or without Venous Thromboembolism

Abstract: Background: Although some studies evaluated venous thromboembolism (VTE) prevalence in patients with chronic obstructive pulmonary disease (COPD), they contain no detailed description of the patients’ characteristics. Objectives: It was the aim of this study to investigate the frequency and clinical characteristics and outcomes of VTE in patients with COPD exacerbation. Methods: Between October 2004 and February 2005, 120 consecutive patients were included in the study. On admission, Doppler examination of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Patients received controlled oxygen therapy via nasal cannula, and antibiotic agents, histamine-2 receptor blockers, bronchodilators and/or steroids were administered. Several previous studies have reported that patients with severe COPD are more likely to have venous thromboembolism [13]; therefore, we routinely used subcutaneous low-molecular-weight heparin in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Patients received controlled oxygen therapy via nasal cannula, and antibiotic agents, histamine-2 receptor blockers, bronchodilators and/or steroids were administered. Several previous studies have reported that patients with severe COPD are more likely to have venous thromboembolism [13]; therefore, we routinely used subcutaneous low-molecular-weight heparin in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…14 Our study identified a small cohort of participants (5.7%) with VTE, which is consistent with some studies with similar prevalence rates. 5,15,16 It should be noted that most studies have examined the prevalence of VTE in the setting of an acute exacerbation, but our cohort reported history of VTE irrespective of exacerbations.…”
Section: Discussionmentioning
confidence: 94%
“…2,3 One study found PE diagnosed by computed tomography (CT) angiography in 25% of individuals presenting with an unknown etiology for a COPD exacerbation. 4 Overall, the reported prevalence of VTE during COPD exacerbations ranges from 5%–29% 5–8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the risk of VTE in chronic obstructive pulmonary disease (COPD) exacerbation ranges from 5% to even 29%. [15][16][17][18] Postmortem examination of patients who died due to COPD exacerbation have demonstrated pulmonary embolism (PE) in 28-51% of cases. 19,20 Lung cancer is a well-established potent risk factor for developing VTE.…”
Section: Introductionmentioning
confidence: 99%